2021
DOI: 10.3389/fvets.2021.683858
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Cardiovascular Activation During Aggressive Reactivity in Dogs

Abstract: Our aim was to investigate cardiovascular activation by measuring changes in facial and body surface temperature using infrared thermography, and neuroendocrine activation using salivary cortisol (CORT) and serotonin concentration (SER) in dogs exhibiting aggressive reactivity in real time. Based on two factors, owner-reported past aggressive behaviors, and detailed behavioral observations collected during a Socially Acceptable Behavior test consisting of 16 subtests and, each individual was categorized as agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…Descriptions of the subtests are presented in the Table 1 . The test was performed outdoors in an enclosed test area of 700 m 2 ( 8 ). The owner/handler passively guided the dog on a leash during subtests 1–7 and 16 and was absent during subtests 8–15, when the dog was alone and attached with a fixed leash.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptions of the subtests are presented in the Table 1 . The test was performed outdoors in an enclosed test area of 700 m 2 ( 8 ). The owner/handler passively guided the dog on a leash during subtests 1–7 and 16 and was absent during subtests 8–15, when the dog was alone and attached with a fixed leash.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is suitable to assess behavioral phenotypes by including dogs with different behavioral backgrounds. For example, the selection of dogs in the study presented in this manuscript was based on Haverbeke et al ( 7 ), who found frequent aggression of military dogs in the SAB test and on our previous findings, which showed that privately owned but highly trained dogs rarely expressed aggression in the SAB test ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, they show left-biased wagging, hence right hemisphere activation, for stimuli that elicit withdrawal (e.g. when shown an unfamiliar, dominant dog or when in aggressive situations) [8,[18][19][20]. Dogs also perceive wagging asymmetries in robot dogs [21] and conspecifics [22].…”
Section: Tail Wagging and Tinbergen's Four Questionsmentioning
confidence: 98%
“…Alternatively, or in addition, past inconsistencies may have arisen because tail wagging is typically analysed as one broad behavioural category, without taking into account its multidimensional nature and parameters (which might be modulated by different arousal, and hence cortisol, levels). This could explain why one study found that aggressive dogs wagged their tails more (and had lower serotonin levels) than non-aggressive dogs—a result that is counterintuitive to the widely held human belief linking tail wagging to positive valence in dogs [ 19 ].…”
Section: Tail Wagging and Tinbergen's Four Questionsmentioning
confidence: 99%
“…Si se les describe en términos neuropsicológicos, los ejercicios con perros pueden presentar en el animal emociones negativas que incluyen miedo, ira y pánico, así como aspectos positivos que incluyen comodidad, vitalidad, euforia y alegría, sin contar los cambios neuroendocrinos y cardiovasculares (Gobbo y Zupan, 2021). Por otro lado, para afrontar una situación estresante especialmente en perros policía con experiencia, los mismos adoptan diferentes estrategias frente a un desafío social inesperado a corto plazo (por ejemplo, un ser humano amenazando a un canino) (Horváth et al, 2007), similar a los distractores ocasionados por otros animales, la temperatura, el tipo de suelo, la lluvia o cualquier cambio físico puede alterar el proceso de búsqueda y rescate, según se ha podido observar en esta investigación.…”
Section: Planes De Acciónunclassified